Les changements de température et de précipitations au Canada - Zhang, X.; Flato, G.; Kirchmeler, M.; Vincent, L.; Wan, H; Wang, X.; Rong, R.; Fyfe, J.; Li, G.; Kharin, V. V. (2019)
Keywords: Ouvrage_Collectif_Numéro1

The role of place meanings in opposition to water-related infrastructure projects: the case of the Mactaquac Dam, New Brunswick, Canada - Reilly, Kate H.; Adamowski, Jan F.; John, Kimberly (Ecology and Society, 2019)

Contribution of Overland and Tile Flow to Runoff and Nutrient Losses from Vertisols in Manitoba, Canada - Kokulan, Vivekananthan; Macrae, M. L.; Lobb, D. A.; Ali, G. A. (Journal of Environmental Quality, 2019)
This study quantified the contributions of overland and tile flow to total runoff (sum of overland and tile flow) and nutrient losses in a Vertisolic soil in the Red River valley (Manitoba, Canada), a region with a cold climate where tile drainage is rapidly expanding. Most annual runoff occurred as overland flow (72–89%), during spring snowmelt and large spring and summer storms. Tile drains did not flow in early spring due to frozen ground. Although tiles flowed in late spring and summer (33–100% of event flow), this represented a small volume of annual runoff (10–25%), which is in stark contrast with what has been observed in other tile‐drained landscapes. Median daily flow‐weighted mean concentrations of soluble reactive P (SRP) and total P (TP) were significantly greater in overland flow than in tile flow ( p < 0.001), but the reverse pattern was observed for NO 3 –N ( p < 0.001). Overland flow was the primary export pathway for both P and NO 3 –N, accounting for >95% of annual SRP and TP and 50 to 60% of annual NO 3 –N losses. Data suggest that tile drains do not exacerbate P export from Vertisols in the Red River valley because they are decoupled from the surface by soil‐ice during snowmelt, which is the primary time for P loss. However, NO 3 –N loading to downstream water bodies may be exacerbated by tiles, particularly during spring and summer storms after fertilizer application. Core Ideas Overland flow was the primary pathway for runoff and nutrient loss at field edge. Most runoff and nutrient loss occurred during spring snowmelt and rain events. Tile drains are unlikely to exacerbate P losses from Vertisolic soils. Tile drains may enhance N loading in this region.

Modelling the impacts of climate change on riverine thermal regimes in western Canada's largest Pacific watershed. - Islam, Siraj ul; Hay, Rachel W.; Déry, Stephen J.; Booth, Barry P. (Scientific Reports, 2019)
Quantification of climate change impacts on the thermal regimes of rivers in British Columbia (BC) is crucial given their importance to aquatic ecosystems. Using the Air2Stream model, we investigate the impact of both air temperature and streamflow changes on river water temperatures from 1950 to 2015 across BC’s 234,000 km2 Fraser River Basin (FRB). Model results show the FRB’s summer water temperatures rose by nearly 1.0°C during 1950–2015 with 0.47°C spread across 17 river sites. For most of these sites, such increases in average summer water temperature have doubled the number of days exceeding 20°C, the water temperature that, if exceeded, potentially increases the physiological stress of salmon during migration. Furthermore, river sites, especially those in the upper and middle FRB, show significant associations between Pacific Ocean teleconnections and regional water temperatures. A multivariate linear regression analysis reveals that air temperature primarily controls simulated water temperatures in the FRB by capturing ~80% of its explained variance with secondary impacts through river discharge. Given such increases in river water temperature, salmon returning to spawn inthe Fraser River and its tributaries are facing continued and increasing physical challenges now and potentially into the future.

Le contexte national et mondial des changements régionaux au Canada - Cohen, S; Bush, E; Zhang, X; Gillett, N; Bonsal, B; Derksen, C; Flato, G; Greenan, B; Watson, E (2019)
Keywords: Ouvrage_Collectif_Numéro1

Évolution de la disponibilité de l'eau douce à l'échelle du Canada - Bonsal, B. R.; Peters, D. L.; Seglenieks, F.; Rivera, A.; Berg, A. (2019)
Keywords: Ouvrage_Collectif_Numéro1

Spaceborne L-Band Radiometry in Environment and Climate Change Canada (ECCC)’S Numerical Analysis and Prediction Systems - Belair, Stephane; Carrera, Marco L.; Abrahamowicz, Maria; Alavi, Nasim; Badawy, Bakr; Shahabadi, Maziar Bani; Bilodeau, Bernard; Charpentier, Dorothee; Deacu, Daniel; Durnford, Dorothy; Gaborit, Etienne; Gasset, Nicolas (IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium, 2019)

Using bootstrap ELM and LSSVM models to estimate river ice thickness in the Mackenzie River Basin in the Northwest Territories, Canada - Barzegar, Rahim; Ghasri, Mahsa; Qi, Zhiming; Quilty, John; Adamowski, Jan (Journal of Hydrology, 2019)

Future realities of climate change impacts: an integrated assessment study of Canada - Akhtar, Mohammad Khaled; Simonovic, Slobodan P.; Wibe, Jacob; MacGee, James (International Journal of Global Warming, 2019)
This paper presents an integrated assessment model for use with climate policy decision making in Canada. The feedback based integrated assessment model ANEMI_CDN represents Canada within the global society-biosphere-climate-economy-energy system. The model uses a system dynamics simulation approach to investigate the impacts of climate change in Canada and policy options for adapting to changing global conditions. The disaggregation techniques allow ANEMI_CDN to show results with various temporal resolutions. Two Canadian policy scenarios are presented as illustrative examples to map policy impacts on key model variables, including population, water-stress, food production, energy consumption, and emissions under changing climate over this century. The main finding is a significant impact of a carbon tax on energy consumption. Two policy scenario simulations provide additional insights to policy makers regarding the choice of adaptation/mitigation options along with their implementation time.

Social participation in older women and men: differences in community activities and barriers according to region and population size in Canada - Naud, Daniel; Généreux, Mélissa; Bruneau, Jean-François; Alauzet, Aline; Levasseur, Mélanie (BMC Public Health, 2019)
Social participation is a modifiable health determinant influenced by physical and social aspects of the environment. Little is known about aging women’s and men’s community activities and barriers according to region and population size. This study compared social participation, desire to participate more, and perceived barriers of aging women and men by Canadian region and population size.
Keywords: Généreux_Mélissa

Risques d’inondation et vulnérabilité : l’exemple du bassin versant de la rivière Kennebecasis, Nouveau-Brunswick, Canada. - Fortin, Guillaume; Poirier, Charlotte; Duhamel, Françis; Germain, Daniel (2019)
La province du Nouveau-Brunswick, situee dans l’est du Canada, est tres affectee par les inondations. Bien que moins documentee que l’alea, la dimension humaine du risque que represente la vulnerabilite est importante pour l’adaptation des populations. Cet article fait un survol des principaux concepts lies a la vulnerabilite et presente leur application a l’echelle d’un bassin versant de taille moyenne. Les resultats montrent la necessite de considerer simultanement la perception et la preparation au risque d’inondation. En effet, si certains residents dans les zones a risque ont une bonne connaissance des inondations et une perception realiste du risque, cela ne se traduit pas necessairement par une preparation adaptee et adequate face au risque. La reduction du risque passe indeniablement par une meilleure sensibilisation et education de la population.